Hidden chromosomal abnormalities in pleuropulmonary blastomas identified by multiplex FISH - Coze Carole; Intagliata Dominique; Rome Angelique; Chrestian Marie-Anne; Bouvier Corinne; Andre Nicolas; Quilichini Benoit; Lena Gabriel; Zattara Helene (BMC Cancer, 2006)
Abstract Background Pleuropulmonary blastoma (PPB) is a rare childhood dysontogenetic intrathoracic neoplasm associated with an unfavourable clinical behaviour. Cases presentation We report pathological and cytogenetic findings in two cases of PPB at initial diagnosis and recurrence. Both tumors were classified as type III pneumoblastoma and histological findings were similar at diagnosis and relapse. In both cases, conventional cytogenetic techniques revealed complex numerical and structural chromosomal abnormalities. Molecular cytogenetic analysis (interphase/metaphase FISH and multicolor FISH) identified accurately chromosomal aberrations. In one case, TP53 gene deletion was detected on metaphase FISH. To date, only few cytogenetic data have been published about PPB. Conclusion The PPB genetic profile remains to be established and compared to others embryonal neoplasia. Our cytogenetic data are discussed reviewing cytogenetics PPBs published cases, illustrating the contribution of multicolor FISH in order to identify pathogenetically important recurrent aberrations in PPB.